Higher Productivity and Profitability in maize systems by nutrient management - Jat, S. L.; Parihar, C. M.; Singh, A. K. (Indian Farming, 2015)
Maize was traditionally grown as subsistence crop in rainfed ecologies till 2000 and hence there exist large management yield gaps in which large proportion was contributed by imbalance and inappropriate plant nutrition with multiple nutrient deficiencies. After 2005, maize grew at very faster rate in terms of area expansion in non-traditional assured ecologies replacing less remunerative crop due to higher productivity. In this context, for enhancing and sustaining higher maize productivity and profitability will be based on balanced adequate fertilization in maize systems using all available organic and inorganic sources with proper crop rotations and timing of application.